Does Effectiveness of Weight Management Programs Depend on the Food Environment?. (23rd September 2018) - Tarlov, Elizabeth; Wing, Coady; Gordon, Howard S.; Matthews, Stephen A.; Jones, Kelly K.; Powell, Lisa M.; Zenk, Shannon N.
Abstract : Objective: To estimate the causal effects of a population‐scale behavioral weight management program and to determine whether the program's effectiveness depends on participants' geographic access to places to purchase healthy and less healthy foods. Data Sources: Secondary data from U.S. Department of Veterans Affairs clinical and administrative records (2008–2014), retail food environment measures from commercial databases (2008–2014), and the American Community Survey (2009–2014). Study Design: We estimated the effect of the VA's MOVE! weight management program on body mass index after 6 months using difference‐in‐difference regressions to compare participants with a propensity score‐matched control group. We estimated treatment effects overall and in subgroups with different access to supermarkets, fast‐food restaurants, and convenience stores. Principal Findings: MOVE! reduced BMI by about 0.71 units among men and 0.70 units among women. The program was slightly less effective for men living near fast‐food restaurants or convenience stores. We found no evidence that treatment effects varied with the food environment among women. Conclusions: The residential food environment modestly alters MOVE! effectiveness among men. A greater understanding of environmental barriers to and facilitators of intentional weight loss is needed. This study highlights important potential intersections between health care and the community.